High matrix stiffness accelerates migration of hepatocellular carcinoma cells through the integrin β1-Plectin-F-actin axis - Zhihui Wang; Wenbin Wang; Qing Luo; Guanbin Song (BMC Biology)
Abstract Background Abundant research indicates that increased extracellular matrix (ECM) stiffness significantly enhances the malignant characteristics of hepatocellular carcinoma (HCC) cells. Plectin, an essential cytoskeletal linker protein, has recently emerged as a promoter of cancer progression, particularly in the context of cancer cell invasion and metastasis. However, the responsiveness of plectin to changes in ECM stiffness and its impact on HCC progression remain unclear. In this study, we aimed to investigate whether plectin responds to variations in ECM stiffness and to explore its involved molecular mechanisms in regulating HCC cell migration. Results Our results showed that, when compared with control group (7 kPa), high ECM stiffness (53 kPa) boosts HCC cell migration by upregulating plectin and integrin β1 expression and increasing F-actin polymerization. Knockdown of integrin β1 negated the high stiffness-upregulated plectin expression. Furthermore, reducing either plectin or integrin β1 levels, or using latrunculin A, effectively prevented the high ECM stiffness-induced F-actin polymerization and HCC cell migration. Conclusions These findings demonstrate that integrin β1-plectin-F-actin axis is necessary for high matrix stiffness-driven migration of HCC cells, and provide evidence for the critical role of plectin in mechanotransduction in HCC cells.